ANALYZING THE EFFECT OF STRESS AND TASK CONFLICTS TOWARD EMPLOYEE PERFORMANCE AT PT. BANK NEGARA INDONESIA (PERSERO) TBK. MANADO - Agustian, Desberini Enestha (Universitas Sam Ratulangi, 2015)
Nowadays, employee often face Stress and Task Conflicts, because there will always be people or things that make them uncomfortable; and it includes people with different opinion whether it as at home or workplace. The researcher did this research in PT. Bank Negara Indonesia (BNI Bank) Persero Tbk. Manado. The purpose of this study is to analyze the effect of Stress and Task Conflicts on Employee Performance. In this research the researcher uses Associative method with Multiple Regression Analysis technique with the population is the permanent employees of BNI Bank Manado and the sample size is 30 permanent employees by using convenience sampling method. The result shows that Stress and Task Conflicts have a strong association to employees. Stress and Task Conflicts have no significant effect to Employee Performance, it means that in that workplace have no Stress and Task Conflict. Stress and Task Conflicts can be occur to an employee but can not be influence to the all employees at BNI Bank Manado. BNI Management has to keep the existing performance and create the good work environment to make the employees spared from Stress and Task Conflicts in order to produce best performance. Â Keywords: stress, task conflicts, employee performance